Wood, Chemical, and Pulp Properties of Woods from Less-Utilized Fast-Growing Tree Species Found in Naturally Regenerated Secondary Forest in South Kalimantan, Indonesia. (3rd July 2016) - Istikowati, Wiwin Tyas; Aiso, Haruna; Sunardi,; Sutiya, Budi; Ishiguri, Futoshi; Ohshima, Jyunichi; Iizuka, Kazuya; Yokota, Shinso
Abstract : This study aimed to identify fast-growing tree species suitable for pulpwood obtained from a secondary forest in South Kalimantan, Indonesia. Chemical and pulp properties were determined for terap ( Artocarpus elasticus Reinw. ex Blume), medang ( Neolitsea latifolia (Blume) S. Moore), and balik angin ( Alphitonia excelsa (Fenzel) Reissek ex Benth). The mean values of ethanol-toluene extract and total lignin contents in terap, medang, and balik angin were 1.5 and 29.7, 2.1 and 25.0, and 3.0 and 24.6%, respectively. A significant negative correlation (r = −0.573) was obtained between lignin content and pulp yield, suggesting that low lignin content in these woods leads to high kraft pulp yields. On the basis of these results, it can be considered that medang and balik angin woods are promising raw materials for bleached pulp, whereas terap wood is suitable for unbleached pulp.